Whey protein (amyloid)-aggregates in oil-water systems: The process-related comminution effect - Heyn, Timon R.; Uttinger, Maximilian; Kwade, Arno; Peukert, Wolfgang; Keppler, Julia K.; Schwarz, Karin (Journal of Food Engineering, 2021)
Whey protein fibrils are excellent emulsifiers. However, the emulsification process significantly alters the size of the aggregates and thus their functionality. It is not yet known how strongly the disperse phase (oil) contributes to the size change. Furthermore, it is unknown whether the aggregate morphologies (semi-flexible amyloid-, and flexible amyloid-like aggregates) differ in their size reduction during emulsification. Therefore, both types of aggregates were processed under different stress levels and in the presence and absence of an oil phase by rotor-stator dispersion, ultrasonication and high-pressure homogenisation. The size reduction exponent for each aggregate type was determined by atomic force microscopy, analytical ultracentrifugation and dynamic light scattering. Semi-flexible fibrils decreased in length by rotor-stator shear from 6200 to a minimum of 190 nm, but sonication resulted in even greater shortening (150 - 84 nm) and is comparable to high pressure homogenisation (283 - 111 nm). Worm-like flexible aggregates are only affected by sonication (98 - 46 nm). The addition of oil resulted in a further reduced aggregate length with lower energy input for all aggregates. Overall, these results provide new insights about the emulsion processing behaviour of different amyloid aggregates, which should be taken into account when preparing emulsions
Keywords: Length reduction; Processing; Emulsification; Fibrils; Rotor-stator shear; Beta-lactoglobulin; Amyloid aggregates